Sliding mode control of pam actuator in LabVIEW environment - Gyeviki, János; Sárosi, József; Véha, Antal; Toman, Péter (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
As an important driver element, the pneumatic artificial muscle (PAM) is widely used in industrial applications for many automation purposes thanks to their variety of advantages. The design of a stable robust position controller for PAM is difficult since it is a very nonlinear time-variant controlled plant because of the compressibility of air, air mass flow rate through the valve, etc. The main contribution of this paper is a robust position control method based on sliding mode for pneumatic muscle actuator. Finally, it presents experimental results.